Paciente pediátrico femenino de 7 Meses de edad con anemia severa - Bustamante Santamaria, Katherine Estefanía (2018)
The present clinical case is intended to analyses all existing types of anemia, in order to reach the conclusion that; Children under 5 years of age have the highest prevalence of iron deficiency anemia in the world. Iron-deficiency anemia occurs when the body does not have sufficient quantity. Iron helps to produce red blood cells. So it was sought with this case study to raise awareness of the importance of breast milk in the first months of life of children, so that they do not fall into an anemia, because of nutrient deficiency due to the lack of exclusive breastfeeding and the deficit Of a good food for its optimal development and growth. Applying the nursing care process could be assessed according to one of the theorizers that resemble the case, and a good diagnosis of assessment by process of nursing care was reached